Spatiotemporal evolution of ecosystem services and its potential drivers in coalfields of Shanxi Province, China - Huanhuan Pan; Jianqing Wang; Ziqiang Du; Zhitao Wu; Hong Zhang; Keming Ma (Ecological Indicators, 2023)
Coal contributes considerably to economic and social development. Its economic benefits have been in focus, whereas the ecosystem services (ESs) that coalfields provide have been largely neglected, and the research on driving force is not deep enough. We estimated soil conservation level, water yield, and habitat quality using the Integrated Valuation of Ecosystem Services and Tradeoffs model; evaluated carbon sequestration using the Carnegie-Ames-Stanford approach; and quantified windbreak and sand fixation using the revised wind erosion equation, based on multi-source data from coalfields in Shanxi Province, China, from 1986 to 2020. Additionally, we identified the dominant effects of the single drivers, and their interactions on ESs, using the geographical detector model. Thereafter, the relative contribution of natural factors and anthropogenic disturbance to ESs was quantified. The results showed that (1) The functions of soil conservation, water yield, carbon sequestration, and windbreak and sand fixation greatly improved, whereas the habitat quality decreased slightly from 1986 to 2020. (2) Changes in soil conservation were mainly influenced by temperature, precipitation, digital elevation model (DEM), population size, construction land area, coal mining intensity, industrial output, and land use intensity. Variations in water yield were mainly governed by temperature, precipitation, DEM, population size, construction land area, industrial output, and coal mining intensity. Variations in carbon sequestration were mainly affected by temperature, precipitation, slope, and coal mining intensity. Changes in windbreak and sand fixation services were mainly influenced by temperature, precipitation, slope, DEM, construction land area, coal mining intensity, industrial output, and land use intensity. Changes in habitat quality were mainly influenced by precipitation, slope, DEM, population size, coal mining intensity, industrial output, and land use intensity. (3) The impacts of the interactions between natural and human factors on ESs were more remarkable than those of a single factor. Furthermore, the contribution of natural factors to changes in ESs was dominant, whereas that of human factors was relatively small. Efficient coordination between natural and human forces, as well as ESs, is essential for the long-term evolution of the coalfield ecosystem. Such efforts will provide a scientific foundation for developing land reclamation and ecological restoration.